2022
DOI: 10.3390/s22218214
|View full text |Cite
|
Sign up to set email alerts
|

Optical Rail Surface Crack Detection Method Based on Semantic Segmentation Replacement for Magnetic Particle Inspection

Abstract: Railway damage detection is of great significance in ensuring railway safety. The cracks on the rail surface play a key role in studying the formation and development process of rail damage, predicting the occurrence of rail defects, and then improving the service life of the rail. However, due to the small shape of the cracks, the typical detection method is relatively complicated, and the speed is quite slow. Although traditional magnetic particle inspection technology is fairly accurate at detection, it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 41 publications
0
7
0
1
Order By: Relevance
“…Deep-learning-based algorithms are being widely used in industrial defect detection research in recent years due to their high efficiency and accuracy. Many researchers have devoted themselves to researching industrial defect detection algorithms based on supervised learning algorithms, which significantly depends on labeled defect data [ 24 , 25 , 26 , 27 , 28 , 29 ]. However, due to the hardship of collecting defective samples, it is extremely hard to obtain enough defect data for a deep model to learn its distribution.…”
Section: Related Workmentioning
confidence: 99%
“…Deep-learning-based algorithms are being widely used in industrial defect detection research in recent years due to their high efficiency and accuracy. Many researchers have devoted themselves to researching industrial defect detection algorithms based on supervised learning algorithms, which significantly depends on labeled defect data [ 24 , 25 , 26 , 27 , 28 , 29 ]. However, due to the hardship of collecting defective samples, it is extremely hard to obtain enough defect data for a deep model to learn its distribution.…”
Section: Related Workmentioning
confidence: 99%
“…In paper [ 26 ] it was shown that the curvature graphs of the axis of an exploited railway track clearly differ from the graphs obtained for model layouts; they have a less regular, oscillatory character, which results from measurement error and the deformations of the ballasted track [ 32 , 33 , 34 ]. However, this did not prevent the basic geometrical parameters of the measured layout from being estimated.…”
Section: Determination Of the Curvature Values For The Test Sectionmentioning
confidence: 99%
“…Therefore, the semantic segmentation method is the most effective method for rail surface defect detection. Kou et al [23] developed a fast and cost-effective method for rail surface defect detection using only a low-cost camera through deep learning and semantic segmentation techniques, achieving accuracy comparable to magnetic particle inspection, with the potential to further improve detection speed using high-frequency cameras. Aiming at the problems of small defects and an insufficient number of samples in the detection of rail surface defects, He et al [24] introduced a deformable convolution and attention mechanism in the FPN network to improve the model's ability to detect defects at different scales, and they utilized the migration learning strategy to perform the feature extraction in the new network architecture.…”
Section: Introductionmentioning
confidence: 99%